Protective effects of cytokine combinations against the apoptotic activity of glucocorticoids on CD34+ hematopoietic stem/progenitor cells - Erdem Kuruca, Serap; Çetin, Muzaffer Beyza; Akgün Dar, Kadriye; Özerkan, Dilşad (Springer Science and Business Media LLC, 2019)
Haematopoietic stem cells can self-renew and produce progenitor cells, which have a high proliferation capacity. Chemotherapeutic drugs are toxic to normal cells as well as cancer cells, and glucocorticoids (GCs), which are essential drugs for many chemotherapeutic protocols, efficiently induce apoptosis not only in malignant cells but also in normal haematopoietic cells. Studies have shown that haematopoietic cytokines can prevent the apoptosis induced by chemotherapy and decrease the toxic effects of these drugs. However, the apoptosis induction mechanism of GCs in CD34+ haematopoietic cells and the anti-apoptotic effects of cytokines have not been well elucidated. In this study, we investigated the apoptotic effects of GCs on CD34+, a haematopoietic stem/progenitor cell (HSPC) population, and demonstrated the protective effects of haematopoietic cytokines. We used a cytokine cocktail containing early-acting cytokines, namely, interleukin-3 (IL-3), thrombopoietin, stem cell factor and flt3/flk2 ligand, and dexamethasone and prednisolone were used as GCs. Apoptotic mechanisms were assessed by immunohistochemical staining and quantified using H-scoring. Dexamethasone and prednisolone induced apoptosis in CD34+ HSPCs. GC treatment caused a significant increase in apoptotic Fas, caspase-3, cytochrome c and Bax, but a significant decrease in anti-apoptotic Bcl-2. Furthermore, as expected, cytokines caused a significant decrease in all apoptotic markers and a significant increase in Bcl-2. Thus, our findings suggest that CD34+ HSPCs are an extremely sensitive target for GCs and that cytokines protect these cells from GC-induced apoptosis.
Keywords: CD34(+) haematopoietic stem; Cytokines; Apoptosis; progenitor cells; Glucocorticoids; 3. Good health